Urgensi Menjadikan Hasil Analisis (HA)/Hasil Pemeriksaan (HP) PPATK Sebagai Alat Bukti dalam Perkara TPPU dan TPPT di Indonesia - Sugianto, Fajar; Irawan, Joshua Evandeo (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2024)
The Indonesian Financial Transaction Reports and Analysis Centre (Indonesian: Pusat Pelaporan dan Analisis Transaksi Keuangan, or PPATK) has made several efforts to prevent and combat money laundering and terrorism financing. The main outputs of PPATK are financial intelligence reports known as Analysis Results and Examination Results. To date, these financial intelligence reports cannot be categorized as evidence that can be used by law enforcement officers in investigations or prosecutions. This study uses the Normative Juridical Dogmatic research method, aiming to provide legal arguments regarding the importance of the status of PPATK's financial intelligence reports in investigations/prosecutions as evidence. The novelty of this research lies in how the author attempts to prove that financial intelligence reports can be used as evidence in criminal cases, whereas previous studies have only stated that financial intelligence reports cannot be used as evidence in criminal cases. The findings of this study indicate that PPATK's financial intelligence reports should be admissible as evidence in handling criminal cases, but this is currently hindered by the existing laws on money laundering and terrorism financing. These regulations need to be revised promptly to strengthen the role of PPATK, particularly in the status of financial intelligence reports in supporting criminal cases.